The Creative Work Environment: Manager and Employee Perceptions of Factors that lnfluence Creativity Within Land·Grant Communication Units - Sherrle R. Whaley; Janet L. Henderson (Journal of Applied Communications, 1994)
According to research, environmental factors have the potential to inhibit or enhance creativity, particularly in a work setting.